BODY MASS INDEX, UNDERWEIGHT AND OVERWEIGHT IN CHILDREN 3-5 YEARSOF AGE FROM SKOPJE - Biljana Trpkovska; Lazarova Tosovska, Dobrila; Zafiroska Strateska, Angja; Zafirova, Biljana; Chadikovska, Elizabeta (Macedonian Academy of Sciences and Arts, 2015)
The aim of this research is to present body mass index (BMI) data in children 3–5 years of age from Skopje and provide the information on the prevalence of different categories of nutritional status during the early childhood. Material and methods: The study included 420 preschool children (210 boys and 210 girls). Stature and body weight were measured, and the BMI value was calculated. Twelve anthropometric parameters were measured using standard equipment and measurement technique according to the International Biological Programme. Results: The majority of anthropometrical parameters have shown significant age and sex specific differences in favor of male subjects. Values at the 50th percentile in our male subjects aged 3, 4 and 5 years for the weight-for-age index were 19 kg, 19.1 and 21 kg, respectively whereas in the female subjects the corresponding values were 16.8 kg, 20 kg and 21 kg. The height-for-age index values corresponding to the 50th percentile showed slightly higher values in our male subjects (100 cm, 109.5 cm and 116 cm) than those in our female subjects (102 cm, 108.5 cm and 116 cm). The values of 50th percentile of BMI in our males subjects were 18.1 kg/m², 16.2 kg/m² and 16 kg/m² whereas in our females were 16.5 kg/m², 16.7 kg/m² and 16.4 kg/m². Conclusion: These results show that underweight is a health problem of the rising generation in Skopje and needs to be considered along with the problem of overweight. It is recommended that the detected values could be applied for evaluation of deviations in growth and nutritional status in children aged 3–5.
Keywords: anthropometry; preschool children; underweight; overweight